EBook Interlibrary Loan in American Public Libraries. Issue 2 (14th March 2016) - Ren, Xiaoai
ABSTRACT: In recent years, eBook collections have been increasing at a slow but steady rate in both public and academic libraries. With the increasing eBook collections in libraries and the advancements made in information discovering services, users can now discover materials existing outside of their local library more easily. EBooks also offer the potential for quick interlibrary loan delivery. Ironically, eBook interlibrary loan has not become prevalent in libraries. Many studies have been done to explore eBook licensing and interlibrary loan in academic libraries and to offer practical solutions for eBook interlibrary lending. Few studies have been done in public libraries. This study explores the current practice of eBook interlibrary loan activities in American public libraries. Survey questionnaires were distributed to 118 randomly selected public libraries. Questions focused on current eBook interlibrary loan best practices, issues, and obstacles in American public libraries. Findings from this study indicate eBook ILL is not a priority for the surveyed public libraries, and the adoption rate of eBook ILL in public libraries is much lower than that in academic libraries.